The progress of mindfulness behavior therapy in the preoperative nursing (正念疗法在外科手术患者围手术期护理中的应用进展) - DUAN Qingluan (段青鸾); LIN Ke (林珂) (Association of Integrative Nursing, 2021)
This paper briefly summarized the concept and potential mechanism of action of mindfulness behavior therapy, reviewed studies about mindfulness behavior therapy in the preoperative nursing, discuss the shortcomings for the application, and provided reference for the future development of mindfulness behavior therapy in the preoperative nursing. (本文简要介绍了正念疗法的概念、分类、作用机制, 对国内外关于正念疗法在外科手术患者围手术期护理中的应用及研究进展进行综述, 提出发展中存在的不足与缺陷, 旨在为外科手术患者围手术期护理中开展正念疗法提供干预、借鉴及依据。)